NORMA 17 – First announcement - committee, Conference (NOMAD Nordic Studies in Mathematics Education, 2016)
The eighth Nordic Conference on Mathematics Education, NORMA 17, will take place in Stockholm, Sweden, May 30–June 2, 2017. The theme for the conference is Nordic research in mathematics education ...